Factors Affecting the Price of Housing in Thailand - Assarattana, Pimchanok (2015)
This dissertation examines factors which have an impact on house price in Thai property market which should be monitored in order to prevent the bubble crisis in the market. Factors examined are Consumer price index, Gross domestic product, population, real estate development credit, personal housing credit, unemployment rate, interest rate for housing loan on average and SET Index. In order to examine the relationship between those fundamental factors and house prices index, the mathematical method used is the multiple linear regression model by using quarterly data from 2001-2014. Moreover, this dissertation also discussion about non-numerical factors, such as, the effect of political turmoil on the real estate and other related financial factors. In literature review, the definition of bubble crisis in property market, bubble crisis in Thailand, the importance and effect of it to the whole economy. The result indicates that house price is affect mostly by personal housing credit following by, real estate development credit, population and interest rate.